Integrating Tat Twam Asi in Language Education: Enhancing Cross–Culture Understanding and Community Interaction in Bali - Putu Niken Praweda Yanti; Wicaksana, GDA; I Gede Budasi; Dewa Putu Ramendra (Room of Civil Society Development, 2025)
Effective cross-cultural communication is essential in multicultural environments, particularly in regions with high international engagement like Bali. This study explores the integration of the Tat Twam Asi philosophical principle in language education to enhance cultural awareness among German students in an international language program. Tat Twam Asi, meaning "You are me, and I am you," emphasizes empathy and social harmony, making it relevant for understanding communication norms in Balinese culture. This qualitative research was conducted at Institut Desain dan Bisnis Bali, involving 18 German students. Data were collected through observations, interviews, and document analysis, focusing on the use of German swear words in cross-cultural interactions. The findings indicate that integrating Tat Twam Asi in language education significantly improves students’ sensitivity to cultural norms, reducing the use of offensive expressions and fostering awareness of appropriate language use in Balinese society. Beyond academic implications, this approach is also relevant to the tourism and service industries, where effective communication plays a crucial role in fostering positive interactions between locals and international visitors. This study suggests that embedding cultural values in community-based language education can strengthen intercultural relationships and support sustainable social development. Future research should explore the broader application of this approach in training programs that promote cultural sensitivity in various professional sectors.